Basis of Articulation and the Phonetics-Phonology Interface (Philologia, 2021)
The notion of articulatory basis or setting has acquired very diverse definitions and interpretations over the course of history of phonetic research, in various schools of phonetics and phonology, or even with different authors (see, e.g. Laver 1978; Jenner 2001). For some, it is even questionable if 'basis of articulation' actually exists. For others, however, it is an indispensable tool for explaining various phonetic and phonological phenomena, including their application in a number of professional domains, e.g. from second language teaching to forensic speaker identification.In this paper, we present a review of different approaches to basis of articulation in phonetic literature, with a focus on its understanding in Slavic linguistics (cf. also Kedrova/Borissoff 2013) and our own research (e.g., Kašić 1998, 2000; Božović 2016, 2020). In particular, we show how the understanding of basis of articulation has evolved from the “sum of speech habits” to the “system of speech habits”, thus linking the physiological basis of speech with the phonological system of a language and providing a window for a better understanding of the phonetics-phonology interface.
Keywords: basis of articulation; syllable; phonetics-phonology interface